Pengembangan Buku Pedoman Manajemen Mutu Pengelolaan Pendidikan Islam Inklusi di Madrasah Se-DIY - Srinugraheni, Aninditya; Rohinah, Rohinah; Rohmah, Lailatu (Al-Athfal: Jurnal Pendidikan Anak, 2016)
This research aims to develop a guide book of quality management of inclusive islamic education in Madrasah as effort to realize of implementation of inclusive education which effective and efficient. It becomes very important because management of inclusive education is whole process of joint activities in the field of education which includes planning, organization, management, and evaluation by using and utilizing facilities availables; personnel, material, and spiritual. Optimizing the quality culture in management of inclusive education can be done with the development of the spirits, values and beliefs of the school, development of school climate and school culture.